62‐4L: Late‐News Paper: A Circular Flexible AMOLED Display with a 1‐mm Slim Border. Issue 1 (May 2016) - Lin, Li‐Fong; Tu, Chia‐Hsun; Jen, Ko‐Ruey; Chen, Yi‐Chien; Ma, Chien‐Kai; Wang, Pei‐Yun; Huang, Yu‐Chun; Lin, Kuan‐Heng; Wu, Hsin‐Hui; Yang, Chieh‐Hung; Ho, Shu‐Te; Lin, Jia‐Hua; et al.
Abstract : A 1.26″ circular plastic‐based AMOLED display has been developed for wearable application. By locating gate drivers in the active area and expending active area outside the circuit area of the panel, we successfully realized a display with true circular shape and 1mm slim border, respectively.